Supply chain in Peruvian companies Adaptability of logistics processes - Merino Garcés, Jose Luis; Meleán Romero, Rosana Alejandra; Saravia Ramos, Giuliana Del Pilar; Carhuancho Mendoza, Irma Milagros (Cuadernos de Administración, 2023)
The supply chain is considered a complex and systematic system consisting of a set of interrelated actors and processes through which companies receive sufficient information to satisfy customer needs and desires and meet production and quality standards. The objective of the research is to analyze the performance of supply chains in Peruvian companies, specifying the adaptation capacity of the logistics processes developed. It was based on the positivist paradigm with a quantitative approach. A data collection instrument was designed, emphasizing process management and logistics. The sample was represented by 343 collaborators from the logistics area. The performance of logistics and process management leads to supply chain efficiency between 38.6% and 54.3%, demonstrating the ability to adapt. The demand, the acquisition of inputs or materials, the administration of the space and the management of its processes merge in the chain to be a whole and generate an environment of technological development managed by human capital and whose objective is customer satisfaction. Efficient performance in supply chains will depend on correct logistics planning and process management to generate better organizational results, promote improvement, flexibility and correct resource management.